PERFORMANCE INDICATORS FOR MALAYSIAN FAMILY TAKAFUL OPERATORS - Roja, Muhammad Izzuddin Halim; Zuki, Mohd Faizuddin Muhammad; Ishak, Muhammad Arif Fadilah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
This study examines the determinants of business performance among Malaysian family takaful operators, focusing on both firm-specific factors (Fee & Commission Income, Zakat Paid, Underwriting Risk, Liquidity, and Firm Size) and macroeconomic indicators (GDP Growth and Inflation Rate). Using an 11-year panel dataset (2013– 2022) from nine family takaful operators, this study employs multiple regression models, including Ordinary Least Squares (OLS), Robust OLS, Cluster Robust OLS, and Feasible Generalized Least Squares (FGLS), to ensure the robustness of the findings. The results indicate that Fee & Commission Income (FCI) and Zakat Paid (ZP) positively influence business performance, highlighting their role as key revenue streams and ethical financial indicators in Islamic finance. Conversely, Underwriting Risk (UWR) and Liquidity (LQ) negatively impact performance, suggesting that excessive claims, risk mismanagement, and inefficient liquidity allocation hinder profitability. Interestingly, Firm Size (FS) was found to be insignificant, challenging the assumption that larger operators achieve better financial outcomes. Additionally, Inflation significantly affects business performance, while GDP Growth was found to be insignificant, implying that family takaful participation is more influenced by inflationary pressures than broad economic expansion. This study contributes to theoretical, methodological, and practical advancements in Islamic finance, particularly in understanding the financial sustainability and risk management strategies of takaful operators. The findings provide valuable insights for policymakers, regulators, and industry practitioners, emphasizing the need for effective pricing strategies, investment diversification, and enhanced risk governance. Future research should explore comparative studies across different jurisdictions and incorporate qualitative insights into takaful consumer behavior and operational challenges.